New Perspectives in Forage Crops 2018
DOI: 10.5772/intechopen.69669
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability of US and Czech Phalaris Arundinacea L. Wild and Cultivated Populations

Abstract: The spread of invasive plant species in natural habitats has become a worldwide problem with negative impacts. Phalaris arundinacea, an important forage and ornamental crop, is widespread worldwide. In recent years there has been a massive spread of P. arundinacea across North America and Canada. Production of Phalaris seed as a forage crop occurs in northern Minnesota; seeds are sold throughout the world, particularly in central Europe. We tested genetic similarities and diferences between populations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Thus, range expansion of reed canarygrass in North America was a not result of hybridization among exotic, forage, and native varietas (Nelson et al 2014) despite previous theories to that effect (Lavergne and Molofsky 2007). More recent research using ISSRs on N. America (Minnesota) wild and cultivated samples showed two slightly overlapping groups separating cultivated samples from wild (Kávová et al 2017). Anderson et al (2016) showed that, based on ISSR markers, all European ornamental cultivars were distinct from wild Czech Republic populations (varietas) while the Czech forage 'Chrastava' was similar to wild types.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Thus, range expansion of reed canarygrass in North America was a not result of hybridization among exotic, forage, and native varietas (Nelson et al 2014) despite previous theories to that effect (Lavergne and Molofsky 2007). More recent research using ISSRs on N. America (Minnesota) wild and cultivated samples showed two slightly overlapping groups separating cultivated samples from wild (Kávová et al 2017). Anderson et al (2016) showed that, based on ISSR markers, all European ornamental cultivars were distinct from wild Czech Republic populations (varietas) while the Czech forage 'Chrastava' was similar to wild types.…”
Section: Introductionmentioning
confidence: 94%
“…Herbaria RCG leaf samples, many of which were previously sampled for AFLP or ISSR/SSR analyses (Jakubowski et al 2013;Nelson et al 2014;Kávová et al 2017), were collected from the University of Minnesota Herbarium (Bell Museum of Natural History, St. Paul, MN). This herbarium collection represents early North American RCG germplasm that is highly likely to be native to Minnesota (Merigliano and Lesica 1998;LaVoie et al 2005).…”
Section: Plant Collectionsmentioning
confidence: 99%
See 3 more Smart Citations